Firms' Contribution to the Reconciliation between Work and Family Life - Evans, John M.. (OECD Labour Market and Social Policy Occasional Papers, 2001)
One of the most striking, long-term trends in the labour market has been the increase in the proportion of parents at work. This has been reflected in the increase in the proportion of dual-earner couple families and of lone-parent families where the parent is working. A growing proportion of the workforces of firms is thus heavily involved in family life and responsibilities, in addition to their jobs. The way in which the working arrangements in firms adapt in response to these changes is of crucial importance for the work/family reconciliation. Whatever government policies are put in place, the detailed aspects of the reconciliation are worked out at the level of the workplace, and the job. This paper provides an international comparison of these "family-friendly" work arrangements voluntarily introduced by firms, and discusses some of the factors which might influence and encourage their development. Detailed information on family-friendly arrangements in enterprises is ...